Novel therapeutic targets on the horizon for lung cancer. Issue 8 (August 2016) - Tan, Wan-Ling; Jain, Amit; Takano, Angela; Newell, Evan W; Iyer, N Gopalakrishna; Lim, Wan-Teck; Tan, Eng-Huat; Zhai, Weiwei; Hillmer, Axel M; Tam, Wai-Leong; Tan, Daniel S W
Summary: Lung cancer is a leading cause of cancer-related mortality worldwide, and is classically divided into two major histological subtypes: non-small-cell lung cancer (NSCLC) and small-cell lung cancer (SCLC). Although NSCLC and SCLC are considered distinct entities with different genomic landscapes, emerging evidence highlights a convergence in therapeutically relevant targets for both histologies. In adenocarcinomas with defined alterations such as EGFR mutations and ALK translocations, targeted therapies are now first-line standard of care. By contrast, many experimental and targeted agents remain largely unsuccessful for SCLC. Intense preclinical research and clinical trials are underway to exploit unique traits of lung cancer, such as oncogene dependency, DNA damage response, angiogenesis, and cellular plasticity arising from presence of cancer stem cell lineages. In addition, the promising clinical activity observed in NSCLC in response to immune checkpoint blockade has spurred great interest in the field of immunooncology, with the scope to develop a diverse repertoire of synergistic and personalised immunotherapeutics. In this Review, we discuss novel therapeutic agents for lung cancer that are in early-stage development, and how prospective clinical trials and drug development may be shaped by a deeper understanding of this heterogeneous disease.